Pyosalpinx due to Cronobacter sakazakii in an elderly woman - Satoshi Ohira; Eri Ikeda; Kyosuke Kamijo; Tomokuni Nagai; Koji Tsunemi; Natsuki Uchiyama; Naoki Matsubara; Ryota Tachibana (BMC, 2021)
Abstract Background Cronobacter sakazakii (C. sakazakii) is a bacterium known to cause severe neonatal infections in premature infants with the consumption of contaminated powdered milk formula. Adult infections are rare, and there have been no reports of pyosalpinx due to C. sakazakii to date. Case presentation We report a case of left pyosalpinx due to C. sakazakii in a sexually inactive postmenopausal woman. A 70-year-old woman presented to our hospital with left lower abdominal pain and fever. Abdominal computed tomography disclosed a cystic mass continuous with the left edge of the uterus. Urgent laparotomy revealed a ruptured left pyosalpinx with pus-like content. Left salpingo-oophorectomy, resection of the right tube, and washing of the abdominal cavity with saline were performed. Pathological examination of the left adnexa showed tubal tissue with acute inflammation and inflammatory exudate, which were compatible with pyosalpinx, and pus culture yielded C. sakazakii. Conclusions This is the first case report of pyosalpinx due to C. sakazakii. Cronobacter sakazakii infections in adult women might occur in the elderly, whose immunity has weakened. Further accumulation of cases of C. sakazakii infection is needed to clarify the etiology and behavior of C. sakazakii in adults.